Rapid detection of genetic variants in hypertrophic cardiomyopathy by custom DNA resequencing array in clinical practice. Issue 8 (14th January 2011) - Fokstuen, Siv; Munoz, Analia; Melacini, Paola; Iliceto, Sabino; Perrot, Andreas; Özcelik, Cemil; Jeanrenaud, Xavier; Rieubland, Claudine; Farr, Martin; Faber, Lothar; Sigwart, Ulrich; Mach, François; et al.
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiac disease (1/500) and the most common cause of sudden cardiac death in young people. Pathogenic mutation detection of HCM is having a growing impact on the medical management of patients and their families. However, the remarkable genetic and allelic heterogeneity makes molecular analysis by conventional methods very time-consuming, expensive and difficult to realise in a routine diagnostic molecular laboratory. Method and results: The authors used their custom DNA resequencing array which interrogates all possible single-nucleotide variants on both strands of all exons (n=160), splice sites and 5′-untranslated region of 12 HCM genes (27 000 nucleotides). The results for 122 unrelated patients with HCM are presented. Thirty-three known or novel potentially pathogenic heterozygous single-nucleotide variants were identified in 38 patients (31%) in genes MYH7, MYBPC3, TNNT2, TNNI3, TPM1, MYL3 and ACTC1 . Conclusions: Although next-generation sequencing will replace all large-scale sequencing platforms for inherited cardiac disorders in the near future, this HCM resequencing array is currently the most rapid, cost-effective and reasonably efficient technology for first-tier mutation screening of HCM in clinical practice. Because of its design, the array is also an appropriate tool for initial screening of other inherited forms of cardiomyopathy.